Separable solutions to an interacting human communities model - Skakauskas, Vladas (Mathematical Modelling and Analysis, 2009)
A model for age‐structured human communities is studied taking into account a religion factor. The model describes dynamics of interacting religions which tolerate pairs with different confessions, parents can choose a religion not necessarily their own for their offsprings, but it is forbidden to change a confession for any individual. In the case of stationary vital rates, the existence of separable solutions is studied.First published online: 14 Oct 2010